"Northern Lights:" An Assessment of the Political and Economic Challenges Facing North East England in the Context of Greater Scottish Autonomy. Issue 1 (2nd January 2018) - Shaw, Keith
ABSTRACT: Drawing on recent research on the Anglo-Scottish border, this article examines the social and economic impact of a more powerful Scotland on its "nearest neighbors" in the North East of England. In examining a series of competing narratives that shape how the significance of the Anglo-Scottish border and borderlands have been understood, the discussion begins by highlighting the longevity of a traditional conflictual narrative that a more powerful Scotland will undermine the North East's economic fortunes. The article will further consider the strength of a competitive narrative by capturing how North East reactions to the independence referendum north of the border have been used as a springboard to argue for greater powers to be devolved to the North East itself— and has led directly to a new generation of "Devolution Deals" being offered by the UK Government to the English regions. Thirdly, the article will examine how the discursive space created by the referendum campaign (and outcome) has created the conditions within which a collaborative narrative—highlighting how Scotland and the North East of England have a shared history and common social and economic challenges—has emerged. The article will conclude by considering whether the emergence of a new cross-border relationship between the "Northern Lights" allows the Anglo-Scottish border to be conceptualized more as a "bridge" than a "barrier, " particularly given the UK's recent decision to leave the EU.